2015
DOI: 10.1007/s40735-015-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion Behavior of Calcium- and Phosphorous-Enriched Titanium Oxide Films and Study of Osteoblast Interactions for Dental Implants

Abstract: Titanium (Ti) dental implants are frequently exposed simultaneously to a corrosive environment and cyclic micromovements at implant/abutment and implant/ bone interfaces, becoming part of a tribocorrosion system. Thus, wear debris and corrosion products/ions can be released to peri-implant tissues and induce inflammatory reactions leading to implant failure. Moreover, the poor osseointegration is also one of the main problems affecting dental implants lifetime. Surface modification strategies have been propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 89 publications
(190 reference statements)
4
33
0
12
Order By: Relevance
“…Anyway, even without HA precipitation, samples investigated in this work showed enhanced human osteoblast adhesion when tested in vitro [43,46,47].…”
Section: Anodic Films Composition and Structurementioning
confidence: 79%
See 1 more Smart Citation
“…Anyway, even without HA precipitation, samples investigated in this work showed enhanced human osteoblast adhesion when tested in vitro [43,46,47].…”
Section: Anodic Films Composition and Structurementioning
confidence: 79%
“…During this process, specific ions as Ca and P can be retained in the porous oxide layer [19,20,22]. This is one advantage of this anodic treatment, as the presence of these ions may improve osteointegration [43,46,47].…”
Section: Anodic Films Composition and Structurementioning
confidence: 99%
“…Several studies had shown that MAO treatment on Ti surfaces enhanced its biological response. Alves et al performed PEO on commercial pure Ti and studied the biological properties of Ca‐and P‐enriched layers assessed for osteoblastic cell viability/proliferation ability. The authors concluded that cell viability/proliferation was improved on PEO treated samples.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one may explore the possibility to add different chemical species to the APT coating from those naturally resulting in the dissolved acid electrolyte. Interesting candidate elements are F, Ca and Mg and P, as demonstrated by recent loading carried out on implants coated with nanoporous titania by means of different techniques [22,3233]. We selected Mg, which is essential to all living cells for its interaction with polyphosphate compounds such as ATP, DNA and RNA, required by many enzymes for their functioning, and present in many pharmaceutical products.…”
Section: Resultsmentioning
confidence: 99%